2014
DOI: 10.1118/1.4876379
|View full text |Cite
|
Sign up to set email alerts
|

Structure and adaptation of arteries to pulsatile flow: The case of the ascending aorta

Abstract: Purpose: The objectives are: (i) assess the development of the impedance of some arteries during the first decades of life; (ii) determine the influence of pulse rate in arterial impedance; (iii) compare the structure of some arterial segments with optimized structures with respect to blood flow; and (iv) explain the elongation of the ascending aorta throughout life in healthy subjects. Methods: A model of the arterial network previously developed by the authors, together with data of lengths, diameters, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…The same effect has been observed in rats (Mircoli et al, 1999). Though, according to the model above referred (Silva and Reis, 2014) increased heart rate leads to lower arterial impedance, the observed increased arterial stiffness with heart rate actually increases impedance. Apparently, this behavior does not make sense because easing blood flow is sought to be the objective of the circulatory system.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…The same effect has been observed in rats (Mircoli et al, 1999). Though, according to the model above referred (Silva and Reis, 2014) increased heart rate leads to lower arterial impedance, the observed increased arterial stiffness with heart rate actually increases impedance. Apparently, this behavior does not make sense because easing blood flow is sought to be the objective of the circulatory system.…”
Section: Introductionsupporting
confidence: 63%
“…3). In an artery of diameter D and length L, (aspect ratio x ¼L/D), with pulsatile flow of frequency ω, under pressure difference ΔP the average current I reads (see Silva and Reis, 2014) …”
Section: Microcirculation and Starling Forcesmentioning
confidence: 99%
See 2 more Smart Citations
“…In total 22 arteries were included in the calculation of J. Based on the present model, a recently published study of the arterial structure [25] also showed that, in general arterial lengths are not optimized with respect to hemodynamic performance, and then an explanation was offered for the elongation of the ascending aorta in healthy people during lifetime. The same study also showed that impedance of the ascending aorta, descending aorta and carotid artery decreases during body growth, therefore suggesting a trend for improvement of hemodynamic performance during that period of life.…”
Section: Comparison Of the Results Of The Models Of Murray Wbe And Tmentioning
confidence: 98%